Persistence with oral antiviral therapy in previously untreated patients with chronic hepatitis B in Spain: the EUPTHEA study. Issue 6 (6th June 2014) - Requena, T; Ais, A; Yébenes, M; Casado, M A; Rueda, M; ,
Abstract : Objective: To determine the persistence to oral antiviral therapy or time until change of treatment in previously untreated patients with chronic hepatitis B (CHB). Methods: A prospective observational study was performed on an adult population with CHB who had started oral antiviral therapy. The recruitment period was 2 years, and the individual follow-up period was 1 year. Monitoring was performed by quarterly completion of electronic case reports by the pharmacy services of participating hospitals in the study. Statistical analysis was performed using the statistical programme PASW V.18.0. Results: A total of 584 patients from 33 hospitals throughout Spain were recruited. Almost all of the patients (99.5%) were on monotherapy, though a few patients (0.5%) were on combined therapy. The drugs that were most commonly prescribed for monotherapy were tenofovir (58.2%), entecavir (35.0%) and lamivudine (4.6%). Treatment persistence during the follow-up year was 83.2%. The reason for non-persistence with treatment for the rest of the patients (16.8%) was discontinuation of treatment (90.8%) or change in the active ingredient (9.2%). Conclusions: There is a high rate of therapy persistence in patients with CHB who begin antiviral treatment in Spain. Today, monotherapy is the most frequently used regimen in this patient population, and tenofovir and entecavir are the most commonly used drugs.